Near infrared spectroscopy and multivariate curve resolution-alternating least squares incorporating 13C-NMR information for monitoring epoxy resins reactions - Garrido, Mariano Enrique (2007)
This paper describes how data from two instrumental techniques - near infrared spectroscopy (NIR) and 13C nuclear magnetic resonance ( 13C-NMR) - are combined by means of multivariate curve resolution-alternating least squares (MCR-ALS) to obtain concentration and spectral profiles for the reaction between phenylglycidylether and aniline. The reaction, in stoichiometric proportions, was monitored by both spectroscopic techniques at 95°C. The concentration values obtained by 13C-NMR were used as an equality constraint during the multivariate curve resolution of the near infrared data. The results obtained were recovered without ambiguities: that is to say, there was a unique solution. The goodness of the results was tested by comparing the recovered concentration profiles with the values obtained by high performance liquid chromatography (HPLC) as a reference technique. The statistical tests showed that there were no significant differences between the results of both methods (α = 5%). Also, the recovered spectra were compared with the experimentally recorded spectra for the reagents (i.e. phenylglycidylether and aniline) and the final product and the correlation coefficients were, in all cases, higher than 0.998.